FACTOR ANALYSIS AS A METHOD OF URBAN LAND USE RESEARCH - Pilicheva, М.; Meteshkin, К.; Kondrashchenko, О. (Municipal economy of cities. Series: «Economy science», 2023)
Cities are being rebuilt, expanded, and modernized, and proper land management becomes critical. Factor analysis can help identify areas in need of social investment, ensuring equal access to resources and opportunities for all citizens. Therefore, the relevance of factor analysis in the study of land use in modern conditions does not require discussion. Factor analysis is a statistical method that allows you to study the relationship between numerous variables and reveal the structural features of the data. The importance of the application of factor analysis in the processes of monitoring the use of land in cities lies in the heavy load on the land resources of cities, which requires informed decisions regarding their use. Factor analysis allows identify key factors affecting land use, understand the community's priorities and needs, evaluate the potential of different areas of the city for the placement of objects. Factor analysis also has its advantages and disadvantages. Disadvantages include: subjectivity (since some factors can be subjectively determined, there is a risk of data distortion or misinterpretation), dynamism (cities are dynamic systems. This means that they are constantly changing, and factors that were relevant today may lose their relevance tomorrow), complexity of interpretation (a large number of factors can complicate the process of interpreting the results). Positive aspects of factor analysis should be noted: continuous updating of data (aimed at collecting and obtaining the most recent data for accurate response and development of appropriate solutions), integrating different data sources (which is a combination of traditional and new data sources such as social networks, can help to get a more complete picture of the situation), the use of a multidisciplinary approach (which allows the involvement of experts from various fields and will provide a deeper understanding of the city's problems and needs). Thus, factor analysis in urban planning remains one of the most effective tools for understanding complex relationships in the city. To get the most complete picture of the situation, factor analysis is often combined with other research methods. One example is geographic information systems (GIS). They allow you to visualize the results of factor analysis on maps, which simplifies the decision-making process at the level of urban planning.